A SELF-INSTILLATION EYE DROP (SIED) TECHNIQUE AMONG GLAUCOMA PATIENT: A RECENT COMPREHENSIVE STRUCTURED REVIEW - Norsiah Abdullah; Salizar Mohamed Ludin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This Systematic Literature Review (SLR) explores the effectiveness of the Self-Instillation Eye Drop (SIED) technique among glaucoma patients, a critical component in managing Intraocular Pressure (IOP) and preventing disease progression. Despite the widespread prescription of eye drops for glaucoma management, improper instillation techniques remain a significant barrier to effective treatment, leading to poor medication adherence and suboptimal clinical outcomes. This review systematically examines recent studies on SIED, focusing on the impact of patient education, technique optimization, and adherence interventions. A comprehensive search of three major databases—Scopus, PubMed, and ScienceDirect—yielded 74 studies published between 2020 and 2024, of which 31 met the inclusion criteria. These studies collectively involve over 12,000 glaucoma patients across various settings. The analysis reveals that proper instillation technique, reinforced through patient education and feedback mechanisms such as self-video monitoring, can improve medication adherence by up to 30% and reduce IOP levels by an average of 2.5 mm Hg compared to traditional methods. The findings also highlight those interventions tailored to individual patient needs, including personalized education and continuous monitoring, are crucial in enhancing the effectiveness of the SIED technique. The review concludes that while SIED offers significant potential in improving glaucoma management outcomes, ongoing research and the development of standardized training protocols are essential for broader implementation. These findings provide a foundation for future studies and clinical practices to optimize glaucoma treatment through better self-administration techniques.